POLA ASUH ORANG TUA PADA ANAK TEMPER TANTRUM DI TAMAN KANAK-KANAK VIDYA DHARMA - Wantini, Sri; Ekowati, Wilis Rengganiasih Endah; Dewi, Sukhitta (Jurnal Pencerahan, 2021)
The research on Parenting in Temper Tantrum Children at Vidya Dharma, Deplongan Kindergarten aims to describe parenting, the role of parents and other families, and the attitudes of parents in dealing with temper tantrum children. The observation was done by direct observation. Interviews were conducted in depth with informants, while documentation was done by photographing images that could be used as the research evidence. The validity of the data was measured by extended involvement, increased perseverance and persistence, triangulation, and member check. The data analysis related to parenting patterns in temper tantrum children used an analysis model from Miles and Huberman which included data collection, data reduction, data presentation and drawing conclusions or verification. The results of this study include three findings, namely: (1) parenting in temper tantrum children in Vidya Dharma Kindergarten were in the forms of democracy, and coddle; (2) the role of parents and immediate family members in the process of caring for children temper tantrums included guiding, teaching, and councelling; (3) the attitude of parents in dealing with children who experienced temper tantrums were in the forms of giving opportunity, validating children's feelings, and problem solving .